Generalized head models for MEG/EEG: boundary element method beyond nested volumes - Kybic, Jan; Clerc, Maureen; Faugeras, Olivier; Keriven, Renaud; Papadopoulo, Théo (Physics in medicine and biology, 2006)
Accurate geometrical models of the head are necessary for solving the forward and inverse problems of magneto- and electro-encephalography (MEG/EEG). Boundary element methods (BEMs) require a geometrical model describing the interfaces between different tissue types. Classically, head models with a nested volume topology have been used. In this paper, we demonstrate how this constraint can be relaxed, allowing us to model more realistic head topologies. We describe the symmetric BEM for this new model. The symmetric BEM formulation uses both potentials and currents at the interfaces as unknowns and is in general more accurate than the alternative double-layer formulation.
Keywords: magnetoencefalografie; biologické modely; Models, Biological; algoritmy; elektroencefalografie; Electroencephalography; Humans; hlava; Algorithms; Computer Simulation; Magnetoencephalography; lidé; Head; počítačová simulace